Classificação dinâmica de nós em redes em malha sem fio - Guedes, Diego Américo (2014)
In this work we present and evaluate a modeling methodology that describes the creation of a topology for wireless mesh networks, and how this topology changes over time. The modeling methodology is based on network science, which is a multidisciplinary research area that has a lot of tools to help in the study and analysis of networks. In wireless mesh networks, the relative importance of the nodes is often related to the topological aspects, and data flow. However, due to the dynamics of the network, the relative importance of the nodes may vary in time. In the context of network science, the concept of centrality metric represents the relative importance of a node in the network. In this work we show also that the current centrality metrics are not able to rank properly the nodes in wireless mesh networks. Then we propose a new metric of centrality that ranks the most important nodes in a wireless mesh network over time. We evaluate our proposal using data from a case study of the proposed modeling methodology and also from real wireless mesh networks, achieving satisfactory performance. The characteristics of our metric make it a useful tool for monitoring dynamic networks.